Revitalisation of the Symbolism of the Altar (Batu Dolu) in the Socio-Historical Local Wisdom of the Alor Tribal Community - syarifuddin; Arifin; Muhammad Abdullah; Wahid Hasyim Tra Beni (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
Batu Dolu is a stone altar that historically represented social identity, customary authority, and communal life among the Alor people. This study examines its symbolic significance and the challenges affecting its revitalisation in Alor Regency. Using a qualitative phenomenological approach, data were collected through observation, in-depth interviews, documentation, and thematic analysis. The findings show that Batu Dolu once marked centres of customary governance across Alor’s mountainous and coastal kingdoms and continues to appear in the official emblem of the Alor Regency Government. However, its contemporary use is largely ceremonial and administrative, while its historical and cultural meanings are becoming less familiar to younger generations. Revitalisation is constrained by weak intergenerational transmission, limited participation by women and young people, declining customary institutions, and insufficient integration into education, heritage conservation, tourism, and digital media. The study concludes that Batu Dolu should be revitalised as a living cultural symbol rather than preserved merely as an official emblem. This requires community-based initiatives that combine local education, physical conservation, inclusive participation, and creative cultural representation.